Medico Legal Mediation: Developing an Interdisciplinary Roleplay - Margaret Castles; Bernadette Richards
Creating opportunities for law students to expand their horizons by working with students from other disciplines offers a unique learning opportunity. Authentic simulation exercises offer students a dynamic and engaging learning experience. A multi-media based interdisciplinary medical negligence 'case' developed in partnership between the University of Adelaide Law and Medical schools combines both elements, offering a truly immersive and realistic educational platform for students from both schools. This article outlines the development, implementation and evaluation of this exercise, and provides both philosophical and practical commentary on the challenges and successes experienced in the process. The article arises out of a proof of concept project developed over a three year period at Adelaide Law School that was aimed at exploring the potential for interdisciplinary engagement between medical and law students in a dispute resolution exercise. Three academics were involved - the developer of the initiative, a medico/legal ethicist and law teacher teaching the undergraduate subject Medical Law and Ethics (Associate Professor Bernadette Richards); a medical practitioner and teacher responsible for the management of simulated learning in the Medical School (Dr Adelaide Boylan); and, a mediator and dispute resolver teaching Civil Procedure and Dispute Resolution to mainly final year law students (Margaret Castles). This article explores the rationale behind the initiative and highlights the value of teaching complex practice skills in an interdisciplinary environment. The scope of this model is not limited to the medico-legal environment, it could be expanded to other law subjects and would enrich the learning of students of both law and other disciplines.